PERAN HUKUM PERDATA DALAM PENGEMBANGAN EKONOMI: PERBANDINGAN INDIA DAN RUSIA DALAM KONTEKS BRICS - Widyastuti, Tiyas Vika; Tri Normalita Putri, Ajeng; Agus Finaningrum, Kiki; Nurkhasanah, Aisyatun; Mashdurohatun, Anis; Tri Bawono, Bambang (Fakultas Hukum Universitas Islam Syekh Yusuf, 2024)
This study examines the civil laws of India and Russia in the context of economic growth, focusing on a comparison between the two countries within the BRICS framework. The methodology employed is a literature review to identify differences and similarities in the development of civil laws in India and Russia. The analysis reveals that while India and Russia may not exhibit remarkable environmental performance compared to other BRICS nations, both prioritize environmental sustainability as a primary focus in their economic development policies. The research underscores the role of environmental laws in achieving sustainable impacts on the environment in both countries. Regarding intellectual property, Russia emerges as the most actively involved nation in intellectual property agreements within BRICS, especially when compared to India. Despite differences in trademark registration procedures, both countries demonstrate compliance with an integrated model. The study notes that Russia's intellectual property laws tend to be more general compared to India, which has more specific regulations. Practically, the research suggests the need for continuous efforts to maintain environmental achievements in both countries, with significant potential for collaboration in renewable energy production. In the realm of intellectual property, the identified patterns offer opportunities for collaboration and knowledge exchange between India and Russia. The findings of this study can guide policymakers and stakeholders in formulating strategies for environmental protection and intellectual property management within the BRICS context. This research makes a significant contribution to a deeper understanding of the differences and similarities in civil laws between India and Russia in the context of the BRICS economy. Keywords: BRICS; Civil Law; Consumer Protection; Environmental Protection; Intellectual Property